Study on Stylistic Evolution of Sitar Baaj in 20th and 21st Century: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian classical music from its inception till date has gone through various phases oftransformations and transitions so the sitar music is. In the process it has embraced and rejected anumber of features with maintaining an absolute balance with the old age tradition. From physicalstructures, playing styles (baaj) to its place in the world of Indian music the instrument has gonethrough the sea changes in the musical history. In 20thand 21stcentury in the world of globalizationwith the course of economic flexibility and advancement of technology, society leads to theIncorporation of western values, ideas, technologies and institutions and commoditization of art andmusic. My thesis ―The Stylistic evolution of sitar baaj in 20thand 21stcentury‖ aimed at the holisticresearch of different aspects of sitar music. The research will also try to unfold the musical and nonmusicalfactors worked behind this process of transition.